Re-examining the evidence for a pitch-sensitive region: a human fMRI study using iterated ripple noise - Barker, Daphne; Plack, Christopher J.; Hall, Deborah A. (Oxford Journals, 2012)
Human neuroimaging studies have identified a region of auditory cortex, lateral Heschl’s gyrus (HG), that shows a greater response to iterated ripple noise (IRN) than to a Gaussian noise control. Based in part on results using IRN as a pitch-evoking stimulus, it has been argued that lateral HG is a general ‘‘pitch center.’’ However, IRN contains slowly varying spectrotemporal modulations, unrelated to pitch, that are not found in the control stimulus. Hence, it is possible that the cortical response to IRN is driven in part by these modulations. The current study reports the first attempt to control for these modulations. This was achieved using a novel type of stimulus that was generated by processing IRN to remove the fine temporal structure (and thus the pitch) but leave the slowly varying modulations. This ‘‘no-pitch IRN’’ stimulus is referred to as IRNo. Results showed a widespread response to the spectrotemporal modulations across auditory cortex. When IRN was contrasted with IRNo rather than with Gaussian noise, the apparent effect of pitch was no longer statistically significant. Our findings raise the possibility that a cortical response unrelated to pitch could previously have been errantly attributed to pitch coding.